2009
DOI: 10.3727/096504009789745610
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine Plus Irinotecan as First-Line Weekly Therapy in Locally Advanced and/or Metastatic Pancreatic Cancer

Abstract: Single-agent gemcitabine has been established as standard treatment for advanced pancreatic cancer since clinical studies have shown an improvement in overall survival and significant clinical benefit when compared to the best supportive care despite low overall objective response. Several phase II studies have tested other single agents and different gemcitabine-based regimens in pancreatic cancer, but both response and survival rates have remained low. Irinotecan, a topoisomerase I inhibitor currently approv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 0 publications
1
1
0
1
Order By: Relevance
“…Before 2006, some trials had explored the combination and several achieved positive results. Similar results were reported by Neri et al (2009) with 33 patients enrolled. Of 32 evaluable patients, 10 responded to treatment (2 complete responses and 8 partial responses) and 11 got stable diseases.…”
Section: Gemcitabine/fluorouracil and Alkaloidssupporting
confidence: 89%
See 1 more Smart Citation
“…Before 2006, some trials had explored the combination and several achieved positive results. Similar results were reported by Neri et al (2009) with 33 patients enrolled. Of 32 evaluable patients, 10 responded to treatment (2 complete responses and 8 partial responses) and 11 got stable diseases.…”
Section: Gemcitabine/fluorouracil and Alkaloidssupporting
confidence: 89%
“…In a small trial reported by Neri et al (2009), long median time to progression (9.2 months) and overall survival (11.8 months) were observed in the combination of gemcitabine and irinotecan. However, a multicenter phase III trial (Stathopoulos et al, 2006), which seemed more convincing due to the large sample size and the establishment of control group, did not gain meaningful difference between this combination and gemcitabine alone groups.…”
Section: Discussionmentioning
confidence: 96%
“…Dwa badania z randomizacją nad terapią łączoną gemcytabiną z irinotekanem wskazują także, że połączenie tych związków może być korzystne [52,53]. Połączenie gemcytabiny z uracylem lub tegafurem nie miało przewagi nad stosowaniem gemcytabiny w monoterapii [54].…”
Section: Terapia łąCzona Z Zastosowaniem Gemcytabiny W Zaawansowanym unclassified